Effect of prenatal bisphenol A exposure on early childhood body mass index through epigenetic influence on the insulin-like growth factor 2 receptor (IGF2R) gene. (October 2020) - Choi, Yoon-Jung; Lee, Young Ah; Hong, Yun-Chul; Cho, Jinwoo; Lee, Kyung-Shin; Shin, Choong Ho; Kim, Bung-Nyun; Kim, Johanna Inhyang; Park, Soo Jin; Bisgaard, Hans; Bønnelykke, Klaus; Lim, Youn-Hee
Graphical abstract: Highlights: Prenatal exposure to BPA may affect children's DNA methylation. One region in IGF2R was differentially methylated by prenatal BPA exposure. Methylation of the CpG site at IGF2R at age 2 was associated with BMI at ages 2–8. The effects of DNA methylation on BMI differed by sex. Abstract: Objectives: Epigenetic mechanisms have been suggested to play a role in the link between in utero exposure to bisphenol A (BPA) and pediatric obesity; however, there is little evidence regarding this mechanism in humans. We obtained data on obesity-associated CpG sites from a previous epigenome-wide association study, and then examined whether methylation at those CpG sites was influenced by prenatal BPA exposure. We then evaluated the relationship between CpG methylation status and body mass index (BMI) in a prospective children's cohort at ages 2, 4, 6, and 8 years. Methods: Methylation profiles of 59 children were longitudinally analyzed at ages 2 and 6 years using the Infinium Human Methylation BeadChip. A total of 594 CpG sites known to be BMI or obesity-associated sites were tested for an association with prenatal BPA levels, categorized into low and high exposure groups based on the 80th percentile of maternal BPA levels (2.68 μg/g creatinine), followed by an analysis of the association between DNA methylation and BMI from ages 2–8. Results: There was a significant increase in the methylation levels of cg19196862 ( IGF2R ) in the high BPA group at age 2 years ( p = 0.00030, false discovery rate corrected p < 0.10) but not at age 6. With one standard deviation increase of methylation at cg19196862 ( IGF2R ) at age 2 years, the linear mixed model analysis revealed that BMI during ages 2–8 years significantly increased by 0.49 (95% confidence interval; 0.08, 0.90) in girls, but not in boys. The indirect effect of prenatal BPA exposure on early childhood BMI through methylation at cg19196862 ( IGF2R ) at age 2 years was marginally significant. Conclusions: Prenatal exposure to BPA may influence differential methylation of IGF2R at age 2. This result indicates that a possible sensitive period of DNA methylation occurs earlier during development, which may affect BMI until later childhood in a sex-specific manner.